2014
DOI: 10.1155/2014/573238
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity Assessment of Poly(ɛ‐caprolactone)/Hydroxyapatite Electrospun Fibers for Bone Tissue Engineering Application

Abstract: Electrospinning is useful for fabricating nanofibrous structure with different composition and morphologies. It offers great advantages through its geometrical structure and biomimetic property, which can provide a suitable environmental site for cell growth. The fiber diameter is entangled by the concentration of PCL with some adjustment of parameters during electrospinning process. PCL with lower concentration had bead structure while higher concentration had smooth fiber. The incorporation of nanoparticle h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 22 publications
3
33
0
Order By: Relevance
“…The main objective of this study was to investigate the effect of the incorporation of nHA and TCH on PCL membrane and compare the morphology, wettability and surface roughness. As reported in our previous study (Hassan et al 2014), incorporation of 10% (w/w) nHA in PCL membrane resulted in a membrane with better fiber properties; the present study will focus on morphology, wettability, mechanical analysis, antibacterial ability and drug release of nanofibers composed of pure PCL and 10% (w/w) nHA/PCL membrane.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The main objective of this study was to investigate the effect of the incorporation of nHA and TCH on PCL membrane and compare the morphology, wettability and surface roughness. As reported in our previous study (Hassan et al 2014), incorporation of 10% (w/w) nHA in PCL membrane resulted in a membrane with better fiber properties; the present study will focus on morphology, wettability, mechanical analysis, antibacterial ability and drug release of nanofibers composed of pure PCL and 10% (w/w) nHA/PCL membrane.…”
Section: Introductionmentioning
confidence: 77%
“…1; Table 1). Based on our previous works, 7.5% (w/v) PCL was optimized, since a higher concentration produced an even larger diameter with non-uniform fiber morphology (Hassan et al 2014). The average fiber diameter of PCL fiber was 0.25 ± 0.08 lm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of polymers used to fabricate scaffolds. These polymers include poly(lactic acid) (PLA), poly(caprolactone) (PCL) [2,4,7,8], poly(glycolic acid) (PGA), poly(lactide-co-glycolide) (PLGA) and poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had shown that HAP could facilitate the formation of apatite layers between the implant material and living bone tissue. 50,51 As we know, cytocompatibility is an important prerequisite of scaffolds intended for bone tissue engineering application. The S5 scaffold was selected to evaluate the cytocompatibility because of its better mechanical properties and good apatite-forming ability.…”
mentioning
confidence: 99%